If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + -2) + 4x = 5x + 2 Reorder the terms: 3(-2 + 5x) + 4x = 5x + 2 (-2 * 3 + 5x * 3) + 4x = 5x + 2 (-6 + 15x) + 4x = 5x + 2 Combine like terms: 15x + 4x = 19x -6 + 19x = 5x + 2 Reorder the terms: -6 + 19x = 2 + 5x Solving -6 + 19x = 2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -6 + 19x + -5x = 2 + 5x + -5x Combine like terms: 19x + -5x = 14x -6 + 14x = 2 + 5x + -5x Combine like terms: 5x + -5x = 0 -6 + 14x = 2 + 0 -6 + 14x = 2 Add '6' to each side of the equation. -6 + 6 + 14x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + 14x = 2 + 6 14x = 2 + 6 Combine like terms: 2 + 6 = 8 14x = 8 Divide each side by '14'. x = 0.5714285714 Simplifying x = 0.5714285714
| 5+ql=m | | 5(x+3)=-80 | | 9h-17=4h+13 | | X-5.8=11.7 | | H(x)=2x^2+5x-3 | | x^2+12x+8=-24 | | n^2+10n+25= | | 5y-2y=3y+10 | | 8x^2+7=119 | | 2y-y-2=-2 | | 1.5(3x-6)=3(x-2) | | -x+29=13+2x | | 2x-4+6=36 | | 3n+46=1+38n | | 4(x-5)-3(x+1)-14=-28 | | -20=20-5v | | av-6=k | | x+(x*.0725)=7.45 | | 8y+5y+8= | | 2[4z-1]=3[z+h] | | 62-x=2x+3 | | (12)(b)(13)=338 | | 12xy-16x= | | 3x-24=-72 | | 12y-7=13+2y | | 100y^2+72y-4=0 | | xy+v=3 | | 12y-7=13+2 | | -3(n-3)-(3n-5)=-5+(3n-4) | | 5cosx=2.5 | | 2n=400 | | 4y-3(5c-2x+2)= |